THE ADDITION EFFECT OF SCAPULOTHORACIC JOINT MOBILIZATION IN INTERVENTION OF ULTRASOUND AND GLENOHUMERAL JOINT MOBILIZATION IN INCREASING RANGE OF MOTION AND FUNCTIONAL ABILITY IN INDIVIDUAL WITH FROZEN SHOULDER - Ni Komang Ayu Juni Antari; Gede Parta Kinandana; Anak Agung Gede Angga Puspa Negara (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2021)
Frozen shoulder or commonly known as adhesive capsulitis is a condition of inflammation in the joint capsule or capsule that protects the glenohumeral joint. The purpose of this study was to prove the effect of adding scapulothoracic joint mobilization interventions in increasing the range of motion and functional ability in individuals with a frozen shoulder. The design used in this study was experimental with pre and post control group design involving 24 samples divided into two groups. Group 1 received conventional intervention including glenohumeral joint mobilization while Group 2 received the additional intervention, namely scapulothoracic joint mobilization in addition to glenohumeral joint mobilization. Ultrasound was given to both groups as initial therapy. The goniometer was used as a measurement of the shoulder range of motion and SPADI was used to measure the functional ability of the shoulder. Hypothesis testing using the independent sample t-test to compare the two interventions was found to be significantly different with the p-value = 0.000 (p <0.05). It can be concluded that the addition of scapulothoracic joint mobilization to conventional interventions proved to be effective in increasing the range of motion and functional ability of the shoulder in individual with frozen shoulder Keywords: frozen shoulder, scapulothoracic joint mobilization, glenohumeral joint mobilization, ultrasound, range of motion, SPADI